Gender differences in the effectiveness of public education messages aimed at smartphone use among young drivers. (17th February 2020) - Gauld, Cassandra S.; Lewis, Ioni M.; White, Katherine M.; Watson, Barry C.; Rose, Chae T.; Fleiter, Judy J.
Abstract: Objective: The main aim of this survey study was to evaluate the relative persuasiveness of three newly developed and piloted public education messages aimed at monitoring/reading social interactive technology on a smartphone among young male and female drivers. In accordance with the Step Approach to Message Design and Testing, the messages were evaluated on a number of outcome measures and also explored the influence of self-reported involvement in the target behavior. Methods: Participants ( N  = 152; 105 F) were aged 17 to 25 years ( M age = 20.14 years, SD  = 2.35) and were randomly allocated to either an intervention (one of the three messages) or control (no message) condition. The messages in the intervention group were assessed on acceptance (i.e., behavioral intention and message effectiveness), rejection, and the third person effect (TPE) differential score (i.e., the message is perceived to be more effective for others than for themselves). Results: Hierarchical regression analyses found that, compared to males, females reported: a) lower intention to monitor/read social interactive technology on a smartphone while driving, b) lower rejection; and, c) lower TPE likelihood, irrespective of message. Conclusions: These findings suggest that young male drivers and young female drivers require different message content to be effective and support the importance of including multiple outcome measures to explain the messages' persuasive effects.